Elevation-based Differentiation in Moisture and Nutrients of Sedimentary Layer in the Water-Level Fluctuation Zone of the Three Gorges Reservoir, China - HE Pingsheng; LI Jinlin; HE Xiubin; TANG Qiang; WU Shengjun; HUANG Ping (Shuitu Baochi Xuebao)
［Objective］ To investigate the elevation-based differentiation in moisture and nutrients of sedimentary layer in the water-level fluctuation zone (WLFZ) and provide a scientific basis for reservoir management. ［Methods］ The WLFZ of the Three Gorges Reservoir was selected as the research object and layered sample were collected from a representative slope. The particle size distribution, nutrient concentration, and moisture content were measured, and the differences in sediment properties at different elevations were analyzed. ［Results］ 1) The particles of the sediment in the WLFZ were relatively fine, with a median particle size ranging from 6.1 to 13.5 μm and an average of 8.7 μm. No significant difference in median particle size was observed among sediments at varying elevations (p>0.05). The particle size distribution of the sediments was dominated by silt, with an average volume content of 82.7%, and the contents of clay and sand were 14.2% and 3.1%, respectively. 2) The mean total organic carbon (TOC), total nitrogen (TN), and total phosphorus (TP) contents of the sediments in the WLFZ were 18.82, 1.24 and 0.75 g/kg, respectively. The stoichiometric ratios of carbon, nitrogen, and phosphorus (C∶N, C∶P, and N∶P) were 15.25, 25.26 and 1.68, respectively. Significant differences were observed in the overall trends of nutrient content changes with elevation. Specifically, TOC and TN contents increased significantly with increasing elevation (p<0.05), while TP content did not show a clear trend. The stoichiometric ratios of C∶P and N∶P in the sediments increased with increasing elevation, while the C∶N ratio showed no significant trend (p>0.05). 3) The average mass water content of the sediments in the WLFZ was 28.63%, and no significant elevation-based spatial differentiation was observed (p>0.05). 4) The particle size distribution, nutrient content, and moisture content of sediments in the WLFZ were distributed in striated layers formed by alternating high and low values along the profile. ［Conclusion］ There is a significant elevation-based differentiation in the nutrient content of the sediments in the WLFZ of the Three Gorges Reservoir, but there is no significant spatial differentiation in particle composition and mass water content.